HTML5 Leads a Web Revolution. (Communications of the ACM, 2012)
The article considers HyperText Markup Language (HTML) 5, a new standard for the HTML document markup language. HTML5's status as a single specification for a markup language which also incorporates different tenchnologies such as a standard for accessing and manipulating HTML documents, a language to define the appearance of HTML documents and the Javascript computer programming scripting language is considered. HTML5 is examined as part of an overall trend in which the World Wide Web has evolved from a connection of static documents into a platform for application softwares.